Enhancing Students' Mathematical Creative Thinking through Ethnomathematics - Based Differentiated Learning - Ningsih, Ade Gusti; Firmansyah, Firmansyah; Hastuti, Woro Sri; Kawuryan, Sekar Purbarini; Kuswidyanarko, Arief; Rizki, Iqbal Ainur (FKIP Universitas Lampung, 2024)
This study focused on the impact of differentiated learning based on ethnomathematics on students’ mathematical creative thinking skills, with particular attention to the influence of differences in their readiness and initial abilities. The aim of this study is to analyses the efficacy of ethnomathematics-based differentiated learning in enhancing students’ mathematical creative thinking abilities. The study was conducted with 47 students enrolled in the elementary school teacher education program at Yogyakarta State University. The data were collected using a pretest and posttest, employing a descriptive quantitative approach. The findings revealed a notable enhancement in mathematical creative thinking proficiency, with an initial mean score of 68.55 on the pretest, which increased to 86.10 on the posttest following the implementation of an ethnomathematics-based differentiated learning approach. The Shapiro-Wilk normality test, conducted on SPSS 25, indicates that the data are not normally distributed, as the significance value (Sig) is less than α. The Wilcoxon nonparametric test yielded an Asymp. Sig (2-tailed) value of 0.001. The results demonstrate that ethnomathematics-based differentiated learning notably impacts students’ mathematical creative thinking abilities. This approach integrates local culture into mathematics learning, improving concept understanding and encouraging students’ active involvement in discussions and presentations. Developing an approach that combines differentiated strategies with elements of ethnomathematics makes a practical and theoretical contribution to mathematics education. This study confirms that the integration of local culture is relevant in mathematics learning and is essential for shaping future teachers who can create inclusive, adaptive, and meaningful learning environments. Keywords: differentiated learning, ethnomatematics, mathematics creative thinking (MCT).DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1618-1634